Прототипізація UEBA системи - Єременко, Д. М. (ХНУРЕ, 2024)
The work is devoted to the development of a prototype system for detecting anomalous user behavior based on the analysis of their behavioral biometric characteristics to create new ways to provide analytical data to the analyzing service with a description of why the identified actions are considered anomalous.
Keywords: UEBA система